(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
There were 466 children under observation, aged from 1 to 12 months, the children were considered practically healthy and did not receive vitamin D within a month before blood sampling. The level of vitamin 25(OH)D3 less than 30 mmol/l was considered an existing biochemical deficiency. Despite the traditional prevention of rickets, 27.8% had mild and moderate severity, while 72.1% had no clinical signs of rickets. In 86.1% of children with rickets, a low level of 25(OH)D3 in the blood serum was detected. Thus, after the modified prevention of rickets, only in 9.2% of the examined children with signs of rickets, did the level of 25(OH)D3 remain low, while in 90.7% it returned to normal. At the same time, in children without signs of rickets, 14.3% had a low content of 25(OH)D3 in the blood serum, and in 85.7% of children, the level returned to normal. As a result, the correct administration of vitamin D makes it possible to reduce severe forms of rickets and improve the psychomotor development of the child.